Effect of Aerogel Incorporation in PCM-Containing Thermal Liner of Firefighting Garment. (July 2018) - Shaid, Abu; Wang, Lijing; Fergusson, Stanley M.; Padhye, Rajiv
Phase change material (PCM) in firefighting garment enhances protection and comfort. Wearing a protective clothing containing PCM, while fighting the fire, is a direct risk to the wearer as most PCMs used are flammable. This article reports a solution by using aerogel. Thermal liner fabric was treated with PCM and/or aerogel and then their thermal properties were analyzed. It has been found that the mean ignition time of PCM-containing thermal liner is around 3.3 s in current case while this value significantly increased to 5.5 s when the combination of aerogel and PCM was used. Moreover, the weight of the liner fabric with aerogel decreased in comparison to PCM-containing liner. Aerogel also slowed down the spreading of flame in PCM-containing fabric. Aerogel–coated liner showed superior heat resistance and the combination of aerogel with PCM increased the thermal resistance of PCM-containing liner.